2021
DOI: 10.3390/app11083542
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Two Potent Phytotoxic Substances from Afzelia xylocarpa for Controlling Weeds

Abstract: Phytotoxic substances released from plants are considered eco-friendly alternatives for controlling weeds in agricultural production. In this study, the leaves of Afzelia xylocarpa (Kurz) Craib. were investigated for biological activity, and their active substances were determined. Extracts of A. xylocarpa leaf exhibited concentration-dependent phytotoxic activity against the seedling length of Lepidium sativum L., Medicago sativa L., Phleum pratense L., and Echinochloa crus-galli (L.) P. Beauv. Bioassay-guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 73 publications
1
2
0
Order By: Relevance
“…In addition, the I 50 values of the shoot and root growth of the two test plants varied, indicating that the inhibitory activity of the M. tenacissima extracts was species-dependent (Table 1). Similar results of concentration-and species-dependent inhibitory activity for extracts of Garcinia xanthochymus, Nephrolepis cordifolia, Albizia richardiana, Clerodendrum indicum, and Afzelia xylocarpa have also been reported [31][32][33][34][35]. Thus, the growth inhibitory activity of the M. tenacissima leaf extracts against the tested plants suggests that its leaf extracts may contain allelopathic substances.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In addition, the I 50 values of the shoot and root growth of the two test plants varied, indicating that the inhibitory activity of the M. tenacissima extracts was species-dependent (Table 1). Similar results of concentration-and species-dependent inhibitory activity for extracts of Garcinia xanthochymus, Nephrolepis cordifolia, Albizia richardiana, Clerodendrum indicum, and Afzelia xylocarpa have also been reported [31][32][33][34][35]. Thus, the growth inhibitory activity of the M. tenacissima leaf extracts against the tested plants suggests that its leaf extracts may contain allelopathic substances.…”
Section: Discussionsupporting
confidence: 71%
“…Clerodendrum indicum, and Afzelia xylocarpa have also been reported [31][32][33][34][35]. Thus, the growth inhibitory activity of the M. tenacissima leaf extracts against the tested plants suggests that its leaf extracts may contain allelopathic substances.…”
Section: Discussionmentioning
confidence: 99%
“…were investigated as a natural source of herbicides. Krumsri et al [12] have identified vanillic acid and trans ferulic acid as the major bioactive compounds, both being responsible for the phytotoxic activity of Afzelia xylocarpa. The concentration of those compounds and differences in the sensitivity of the plant models are key to their phytotoxic action.…”
Section: Contributionsmentioning
confidence: 99%